Spectral distance on the circle - Martinetti, Pierre (Journal of functional analysis, 2008)
A building block of non-commutative geometry is the observation that most of the geometric information of a compact Riemannian spin manifold M is encoded within its Dirac operator D. Especially via Connes' distance formula one is able to extract from the spectral properties of D the geodesic distance on M. In this paper we investigate the distance d encoded within a covariant Dirac operator on a trivial U ( n ) -fiber bundle over the circle with arbitrary connection. It turns out that the connected components of d are tori whose dimension is given by the holonomy of the connection. For n = 2 we explicitly compute d on all the connected components. For n ⩾ 2 we restrict to a given fiber and find that the distance is given by the trace of the module of a matrix. The latest is defined by the holonomy and the coordinate of the points under consideration. This paper extends to arbitrary n and arbitrary connection the results obtained in a previous work for U ( 2 ) -bundle with constant connection. It confirms interesting properties of the spectral distance with respect to another distance naturally associated to connection, namely the horizontal or Carnot–Carathéodory distance d H . Especially in case the connection has irrational components, the connected components for d are the closure of the connected components of d H within the Euclidean topology on the torus.